Building energy performance a case study at G2 Building UTHM - Abdullah, Kamil; Mohamad, Mohd Hafiz (Penerbit Akademia Baru, 2018)
Improper energy consumption has become a concern among the building owners. To ensure proper energy consumption of the building, it has become a practice to conduct building energy performance study. The study allows the building owner to confirm possible ineffective energy utilization of the building. This paper presents a quantitative analysis of a building performance for G2 Building in Universiti Tun Hussein Onn Malaysia (UTHM) for a duration from August 2016 until March 2017. The study is based on collected electricity consumption data for the interval of 30 minutes every day throughout the study period. Building Energy Index (BEI) and Energy Intensity Index (EII) were used as building performance tools. The calculated BEI is 254.24 kWh/m2/year which is far beyond a minimum of 150 kWh/m2/year for nonresidential building in order to achieve a point by Green Building Index (GBI) of Malaysia. Meanwhile, the results on EII shows that a monthly amount of electricity energy was inconsistently consumed throughout a semester break and lecture period at a G2 Building. The present study attempts to address the building energy performance in G2 Building, hence to build up awareness on energy saving among building users.